AN APPRAISAL OF PROMINENT GREEN MARKETING COMMUNICATION THEMES AS PART OF GREEN MARKETING STRATEGIES (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The present research is an attempt to understand  the role of “green” in the context of green  marketing communications that can influence  the green buying decisions of people. The  existing research in this area has been examined  to identify the major thrust areas that the  firms adhering to green marketing strategies  are emphasizing to influence their customers.  An investigative framework comprising of  prime theme of advertisements of such firms  is created that identifies and classifies various  stakeholders, potentially impacted through the  environmentally friendly effort of a firm. It was  observed that the customers that are sensitised  to the green buying in the area of Prayagraj,  do notice the message of the advertisement and  carry difference in opinions on the impact of  such green marketing communications but the  reflection in their buying preferences are not  consistent with their opinions.
Keywords: Green Marketing; Marketing; Communications; Green Buying Behaviour